THE DAMAGE OF THE OPTIC NERVE AS THE OUTCOME OF UNINTENTIONAL POISONING BY CLOSANTEL - Evgenia Sergeevna Kurakina (University of Brawijaya, 2021)
Background: In recent decades, the problem of toxic damage of the visual system due to poisoning by various medicines has become particularly relevant. The clinical case of a bilateral acute optic neuropathy of toxic genesis in a patient by the unintentional application of closantel used in veterinary practice is presented in the report. Closantel is a structural derivative of the salicylanilides, which is used exclusively in veterinary medicine for the prevention and treatment of large and small-scale cattle. Neurological and ophthalmic symptoms are often associated with the intoxication of closantel.